Describing children at risk: experiments with context. Issue 1 (2nd January 2019) - Ratner, Helene
ABSTRACT: Drawing on science and technology studies (STS), this article explores information practices around children deemed to be 'at risk'. Risk is not a self-evident epistemic object. Different professional instructions mobilize the concept of context to emphasize the partiality and contingency of descriptions of 'risk'. This article develops the concept of 'description device' to account for how the concept of context (1) displaces a teacher's attention from child to context, hence materializing a relational view of the child, and (2) results in written statements rendering children at risk informational. Empirically, it compares how social services and educational psychology enact different 'contexts' in need of teachers' description, and how these descriptions tame the uncertainty deemed to pertain to children at risk. This type of description has consequences not only for the children being described but also for teacher subjectivities. The article concludes that context is both an opaque and generative description device, displacing teachers' attention from child to context. This effects an enlargement of the world but also a teacher subjectivity that is reflexive about the partiality of her descriptions.